If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2c + -1) + -2 = 2c + 3 Reorder the terms: 3(-1 + 2c) + -2 = 2c + 3 (-1 * 3 + 2c * 3) + -2 = 2c + 3 (-3 + 6c) + -2 = 2c + 3 Reorder the terms: -3 + -2 + 6c = 2c + 3 Combine like terms: -3 + -2 = -5 -5 + 6c = 2c + 3 Reorder the terms: -5 + 6c = 3 + 2c Solving -5 + 6c = 3 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. -5 + 6c + -2c = 3 + 2c + -2c Combine like terms: 6c + -2c = 4c -5 + 4c = 3 + 2c + -2c Combine like terms: 2c + -2c = 0 -5 + 4c = 3 + 0 -5 + 4c = 3 Add '5' to each side of the equation. -5 + 5 + 4c = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 4c = 3 + 5 4c = 3 + 5 Combine like terms: 3 + 5 = 8 4c = 8 Divide each side by '4'. c = 2 Simplifying c = 2
| 6(10-3x)=10-8x | | m-20=10 | | 3/14N=3/16 | | (4t+5)(3t+10)=0 | | -8+3x=-4x+55 | | -2(x+1)+x=7-4x | | x-[5+3x-[5x-(6+x)]]=-3 | | 2X=4/15 | | 6x+1=3x+4 | | y+15=-30 | | x-2x+12-3x=-5(x-2)+2 | | 8+3n=-2a+24 | | 2x-6-8=0 | | 4-2x=8+.5x | | -4x-3=6x-123 | | -0x+10-3x=-5(x-2)+2 | | x+22+3x=-19-3x-22 | | -2x+9-3x=-5(x-2)+2 | | -2x+12-3x=-5(x-2)+0 | | -2x+12-3x=5(x-2)+2 | | 4+3x=7x-24 | | 3(s+2)-(2s-3)=5 | | 3x^2-3x=21 | | 3x+8y+2=0 | | 4x=(-8) | | 5/8*8/5 | | -2x+12-3x=-5(x-2)+3 | | 2x+12-2x=-5(x-2)+2 | | 4x+3y-5=0 | | 8+3x=6x+26 | | -4x+12-2x=-5(x-2)+2 | | x+6-x-4=10-x |